Construction and 13C hyperpolarization efficiency of a 180 GHz dissolution dynamic nuclear polarization system. (3rd May 2017) - Kiswandhi, Andhika; Niedbalski, Peter; Parish, Christopher; Ferguson, Sarah; Taylor, David; McDonald, George; Lumata, Lloyd
Abstract : Dynamic nuclear polarization (DNP) via the dissolution method has become one of the rapidly emerging techniques to alleviate the low signal sensitivity in nuclear magnetic resonance (NMR) spectroscopy and imaging. In this paper, we report on the development and 13 C hyperpolarization efficiency of a homebuilt DNP system operating at 6.423 T and 1.4 K. The DNP hyperpolarizer system was assembled on a wide‐bore superconducting magnet, equipped with a standard continuous‐flow cryostat, and a 180 GHz microwave source with 120 mW power output and wide 4 GHz frequency tuning range. At 6.423 T and 1.4 K, solid‐state 13 C polarization P levels of 64% and 31% were achieved for 3 M [1‐ 13 C] sodium acetate samples in 1 : 1 v/v glycerol:water glassing matrix doped with 15 mM trityl OX063 and 40 mM 4‐oxo‐TEMPO, respectively. Upon dissolution, which takes about 15 s to complete, liquid‐state 13 C NMR signal enhancements as high as 240 000‐fold ( P =21%) were recorded in a nearby high resolution 13 C NMR spectrometer at 1 T and 297 K. Considering the relatively lower cost of our homebuilt DNP system and the relative simplicity of its design, the dissolution DNP setup reported here could be feasibly adapted for in vitro or in vivo hyperpolarized 13 C NMR or magnetic resonance imaging at least in the pre‐clinical setting. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Over 60% carbon‐13 polarization was achieved using a low‐cost, homebuilt 180 GHz dynamic nuclear polarization (DNP) system.